A Review Characterizing 25 Ecosystem Challenges to Be Addressed by an Ecosystem Approach to Fisheries Management in Europe - Bastardie, Francois; Brown, Elliot J.; Andonegi, Eider; Arthur, Robert; Beukhof, Esther; Depestele, Jochen; Döring, Ralf; Eigaard, Ole Ritzau; García-Barón, Isabel; Llope, Marcos; Mendes, Hugo; Piet, GerJan; et al. (Frontiers in Marine Science, 2021)
The impacts of fisheries on ocean resources are no longer considered in isolation but should account for broader ecosystem effects. However, ongoing ecosystem-wide changes added to the inherent dynamics of marine ecosystems, create challenges for fisheries and fisheries management by affecting our ability to ensure future fishing opportunities and sustainable use of the seas. By reviewing a corpus of fisheries science literature, we contribute to informing policymakers with considerations of the various threats to fisheries and the marine ecosystems that support them. We identify and describe 25 ecosystem challenges and 5 prominent families of management options to address them. We capture the challenges within three broad categories: i) fishing impacts on the marine environments and future fishing opportunities, ii) effects of environmental conditions on fish and fishing opportunities, and iii) effects of socioeconomics, fisheries management and institutional set-up on fisheries. Our review shows that, while most EU fisheries are facing a similar array of challenges, some of them are specific to regions or individual fisheries. We reflect this in selected regional cases to exemplify the challenges along with fishery-specific cases, among the dramatic Baltic cod situation facing an array of cumulative pressures, moving ecosystem interactions that rely on the North Sea forage fish facing climate change, fishing interactions in a fluctuating mixed fishery in the Celtic Sea, bycatch and habitat degradation in the Bay of Biscay, undercapacity and lack of knowledge on some features of the EU Outermost Regions. We conclude by recognizing knowledge gaps regarding the direction of causality, nonlinear responses and confounding effects. All of the challenges we identify may guide further data collection and research coordination to improve our understanding and to monitor real changes, both of which are required to inform an Ecosystem Approach to Fisheries Management (EAFM). An European EAFM could build upon an array of management measures currently tailored for fisheries management only, including promoting funding interdisciplinary research and ecosystem monitoring. Such integrative management should reduce uncertainties in environmental, social and economic trends, and lower the risk for disruptive events or ecosystem effects with far-reaching consequences, including a shift toward less productive marine ecosystems.